Organizational and performance consequences of management control systems : ERP in small service companies - Mäkelä, Leea (2013)
The purpose of this thesis was to provide knowledge on the organizational and performance consequences of management control systems. The examination into prior literature yielded information on the benefits and challenges related to ERP systems, the position of ERP systems in the overall control environment of the company, and how ERP influences the ensemble of management control systems. By leaning to the prior work of Chapman and Kihn (2009), a survey research was conducted aiming to discover if information system integration (ISI) embedded in ERP supported the enabling approach to management control, and whether this in turn would result into higher performance and perceived system success. The survey data consisted of 42 small service companies in the building technology industry with a particular ERP system in use. Contrary to the prior research, the results of the Pearson’s correlation analysis did not provide support for the relationship between ISI and the enabling approach to management control. This may be caused by the low level of integration in the system. However, the results indicated a statistically significant relationship between the enabling approach to management control and perceived system success. This suggests that by endorsing the enabling approach to management control satisfaction towards the system can be enhanced. Partial support was provided for the relationship between the enabling approach to management control and market performance. The link to financial performance remained unproven which is typical in researching small companies. While this research has several limitations concerning for example the small dataset of the survey, the results seem to coincide with the results of earlier research thus offering valuable insight into the use of ERP systems.